BELIEF, PERCEPTION, AND CHALLENGES OF NON ENGLISH DEPARTMENT STUDENTS TO LEARN ENGLISH IN GLOBALIZATION ERA - Erna Iftanti; Binti Maunah (University of Kuningan, 2021)
This study was carried out in response to the demand that in this 4.0 era, Indonesian students should be proficient in English. Hence, in Indonesia, English has been taught and learnt since elementary school level up to tertiary level of education. This long period of learning should lead the students to be proficient in English which is proved by passing the minimum score of 450 TOEFL test. Yet, many of them did not meet the minimum score. Thus, this study investigates their perception and belief in learning English and the challenge of being able to be proficient in English. The study was done qualitatively through interviewing 80 students of non-English Department who were taking TOEFL course. It reveals that English is perceived like a two-side coin which in one hand, it is misperceived as a difficult subject because of its complicated rules to be memorized. In the other hand, it is thought to be joyful and meaningful that they believe as a means of bringing educational, social, and economical success. Therefore, they are challenged to be proficient in English. This study is then pedagogically implemented through building positive belief and perception that learning English is fun and helpful.Keywords: Belief; perception; challenge; and globalization era